Caso radiológico - Pinto,Mariana (2013)
We present the clinical case of an 11-year-old boy with cerebral palsy. He was observed in the Gastroenterology Department for the presence of recurrent episodes of vomiting (bilious and/or fecaloides) with one year of development, preceded by pallor, sweating, sense of abdominal pain and abdominal swelling. Recently the episodes occur every week. The abdominal Computed Tomography (CT) showed megacolon compatible with the diagnosis of ileocolic intestinal pseudo-obstruction. Laparoscopic cecostomy was performed for decompression of exuberant aerocolia, result of permanent aerophagia typical of adolescents with cerebral palsy, allowing the administration of antegrade enemas in order to improve the constipation.